A REMARKABLE NEW PALEONISCOID FISH (OSTEICHTHYES: ACTINOPTERYGII) FROM THE LOWER CARBONIFEROUS OF TUVA REPUBLIC (RUSSIA) - Prokofiev A.M. (My University, 2004)
An unusual new palaeoniscoid, Senekichthys hirundo gen. et sp. nov., is described from the Lower Carboniferous of the Tuva Republic (Southwestern Siberia) of Russia. In the shape of its anal and caudal fins this new taxon resembles the peculiar palaeoniscoid Dwykia analensis Gardiner, 1969 from the Lower Carboniferous of South Africa, but the very incomplete record of the latter gives no possibility to place both forms in a single family. In general view Senekichthys seems to be most similar to the family Elonichthyidae, but many derived characters occurring in the new taxon (e.g., long and pointed snout, large orbit with regard to the postorbital head length, very long and slim caudal lobe, very long and short-based anal fin, fulcral scales on the upper caudal lobe ending well before its distal tip, absence of ridge scutes, etc.) support its classification outside of the elonichthyids. Therefore Senekichthys is considered as a Palaeoniscimorpha incertae sedis. The Lower Carboniferous fish faunas of Western Siberia are briefly discussed and compared.
Keywords: actinopterygians; Lower Carboniferous; new species; palaeoniscoids; Southwestern Siberia; Paleozoic::Carboniferous; Палеозой::Каменноугольная